PELAKSANAAN E-GOVERNMENT PADA PEMERINTAH DAERAH DI INDONESIA: KEMANDIRIAN DAERAH SEBAGAI VARIABEL MODERASI: IMPLEMENTATION OF E-GOVERNMENT IN REGIONAL GOVERNMENT IN INDONESIA: REGIONAL INDEPENDENCE AS A MODERATING VARIABLE - Ilma, Arini Ilma; Basri, Yesi Mutia; Azlina, Nur (Universitas Riau, 2025)
The purpose of this study was to determine the effect of region, local revenue, and population on the implementation of E-Government with regional independence as an intervening variable. In determining the sample, this study used a purposive sampling technique, namely sampling using criteria based on research policies. Observation data of 123 were taken from 41 districts/cities from a 3 (three) year observation period starting from 2020-2022. The type of data used is quantitative data sourced from secondary sources. Data analysis used multiple linear regression and Conditional Process Analysis from Hayes. The results of the study showed that region, local revenue, and population influenced the implementation of E-Government. Regional independence moderates the effect of local revenue and population on the implementation of E-Government. Meanwhile, regional independence does not moderate the effect of the region on the implementation of E-Government. This study contributes to local governments in the implementation of e-government